COVID-19 pandemic offers rare chance for food systems transformation - Swinnen, Johan; McDermott, John (UN Food Systems Summit 2021, 2021)
The COVID-19 pandemic has caused unprecedented disruptions of social interactions, affecting both the supply and demand for food. These disruptions to jobs, income and food supply magnified and exacerbated existing inequalities. While the emerging urban middle class suffered greater income losses, the poor and vulnerable in rural and urban areas experienced the worst livelihood impacts. Many social programs, including cash transfers, nutrition and education were interrupted, delayed, or halted, setting back decades of process in reducing poverty, hunger, malnutrition and illiteracy. While efforts have been made to address these inequalities, they are likely to persist, as the global vaccine rollout is disproportionately delivering doses to wealthy countries and relatively well-off individuals.